Ultrafast charge transfer processes accompanying KLL Auger decay in aqueous KCl solution - Céolin, Davide; Kryzhevoi, Nikolai V. (Physical review letters, 2017)
X-ray photoelectron and KLL Auger spectra were measured for the K+ and Cl− ions in aqueous KCl solution. While the XPS spectra of these ions have similar structures, both exhibiting only weak satellites near the main line, the Auger spectra differ dramatically. Contrary to the chloride case, a very strong extra peak was found in the Auger spectrum of K+ at the low kinetic energy side of the 1D state. Using the equivalent core model and ab initio calculations this spectral feature was assigned to electron transfer processes from solvent water molecules to the solvated cation. The observed charge transfer processes are suggested to play an important role in charge redistribution following single and multiple core-hole creation in atoms and molecules placed into environment.